Spectrum aware clustering in cognitive radio ad hoc networks - Sagar Anand Ukey, Aishwarya; Chawla, Meenu (International Journal of Engineering and Technology, 2018)
Cognitive radio (CR) is an emerging technology developed for efficient utilization of the radio spectrum. CRN utilizes CR technology and enables the unlicensed users also referred as secondary users (SUs) to access free portions of the licensed spectrum in an opportunistic manner. To support scalability and stability in distributed CRNs also referred as cognitive radio ad hoc networks (CRAHNs), SUs are often organized into smaller groups known as clusters. Spectrum aware clustering is considered as the key technique to overcome numerous is-sues associated with the dynamic nature of CRAHNs. This article focuses on clustering in CRAHNs and presents a comprehensive review of various spectrum aware clustering algorithms presented in the literature. The article highlights notable clustering metrics and includes the description of cluster formation and maintenance process. The article also renders potential research gaps in existing research works and discusses open challenges and issues that need to be addressed for efficient clustering in CRAHNs.Â